INFORMATION SYSTEM USING WEB-BASED RAPID APPLICATION DEVELOPMENT METHOD - Rangga Satria Wirabangsa; Dwi Ratnasari; Giri Wahyu Wiriasto (JUTI: Jurnal Ilmiah Teknologi Informasi, 2023)
The service of recording and borrowing goods at the Teacher Learning Center agency is currently still being carried out manually. parties who will borrow goods must come to the teacher learning center directly and record borrowing data and item data is still done manually, whereas at this time it has entered the era of the industrial revolution 4.0, of course, everything will have efficiency and very fast access. With this problem, of course, the right solution is to have a system that can borrow and record goods based on a website. The process of creating and designing a website uses the Rapid Application Development model, which is a method that starts with the requirements planning stage, RAD design workshop (work with users, build system) and implementation. Testing on the application uses alpha and beta testing, alpha testing uses blackbox testing while for beta testing uses the mean opinion score (MOS). Alpha testing obtained the website running according to what was expected to be successful while beta testing obtained a measurement result score with 10 respondents, namely 88.60% based on alpha testing and beta testing, it was concluded that this website was able to meet and support the needs of users and agencies.